Generation of Distal Airway Epithelium from Multipotent Human Foregut Stem Cells - Hannan, Nicholas R.F. (Stem Cells Dev, 2015)
Collectively, lung diseases are one of the largest causes of premature death worldwide and represent a major focus in the field of regenerative medicine. Despite significant progress, only few stem cell platforms are currently available for cell-based therapy, disease modeling, and drug screening in the context of pulmonary disorders. Human foregut stem cells (hFSCs) represent an advantageous progenitor cell type that can be used to amplify large quantities of cells for regenerative medicine applications and can be derived from any human pluripotent stem cell line. Here, we further demonstrate the application of hFSCs by generating a near homogeneous population of early pulmonary endoderm cells coexpressing NKX2.1 and FOXP2. These progenitors are then able to form cells that are representative of distal airway epithelium that express NKX2.1, GATA6, and cystic fibrosis transmembrane conductance regulator (CFTR) and secrete SFTPC. This culture system can be applied to hFSCs carrying the CFTR mutation Δf508, enabling the development of an in vitro model for cystic fibrosis. This platform is compatible with drug screening and functional validations of small molecules, which can reverse the phenotype associated with CFTR mutation. This is the first demonstration that multipotent endoderm stem cells can differentiate not only into both liver and pancreatic cells but also into lung endoderm. Furthermore, our study establishes a new approach for the generation of functional lung cells that can be used for disease modeling as well as for drug screening and the study of lung development.